Association of Central Obesity and Salty Food Consumption with Small Dense LDL-C in Middle-Aged Indonesian Adults - Rohmaeni, Yeni; Hardinsyah, Hardinsyah; Tanziha, Ikeu (Jurnal Gizi dan Pangan, 2023)
This study aimed to investigate the association between central obesity and salty food consumption with the elevated of Small Dense Low-Density Lipoprotein-Cholesterol (sdLDL-C) among middle-aged Indonesian adults. Dietary behavior, together with the presence of obesity, leads to an increase in sdLDL-C. The study selected 8,611 subjects aged 49–64 years, from secondary data of a population-based survey conducted by the Ministry of Health of the Republic of Indonesia. The sdLDL-C concentration was determined using the Sampson equation. A significant association was observed between salty food consumption (OR=1.20; 95% CI: 1.04–1.38), general obesity (OR=2.59; 95% CI: 2.23–30), central obesity (OR=2.39; 95% CI: 2.11–2.70) and sdLDL-C. Diabetes and hypertension were positively associated with sdLDL-C, whereas Physical Activity (PA) was negatively associated with sdLDL-C. This study showed that obesity and consumption of salty food is associated with the increase of sdLDL-C, whereas PA is associated with the decrease of sdLDL-C.